Comparative demography of Bactrocera dorsalis (Hendel) and Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) on deciduous fruit. Issue 2 (27th April 2020) - Pieterse, Welma; Manrakhan, Aruna; Terblanche, John S.; Addison, Pia
Abstract: Bactrocera dorsalis (Hendel) and Ceratitis capitata (Wiedemann) are highly polyphagous fruit fly species and important pests of commercial fruit in regions of the world where they are present. In South Africa, B. dorsalis is now established in the north and northeastern parts of the country. B. dorsalis is currently absent in other parts of the country including the Western Cape Province which is an important area for the production of deciduous fruit. C. capitata is widespread in South Africa and is the dominant pest of deciduous fruit. The demographic parameters of B. dorsalis and C. capitata on four deciduous fruit types Prunus persica (L.) Batsch, Prunus domestica L., Malus domestica Borkh. and Pyrus communis L. were studied to aid in predicting the potential population establishment and growth of B. dorsalis in a deciduous fruit growing environment. All deciduous fruit types tested were suitable for population persistence of both B. dorsalis and C. capitata . Development was fastest and survival highest on nectarine for both species. B. dorsalis adults generally lived longer than those of C. capitata, irrespective of the fruit types that they developed from. B. dorsalis had a higher net reproductive rate ( R o ) on all deciduous fruit tested compared to C. capitata . However, the intrinsic rate of population increase was estimated to be higher for C. capitata than for B. dorsalis on all fruit types tested primarily due to C. capitata 's faster generation time. Provided abiotic conditions are optimal, B. dorsalis would be able to establish and grow in deciduous fruit growing areas.